What is celebrity populism? The case of the Croatian singer Miroslav Škoro - Šalaj, Berto (Družboslovne razprave, 2022)
The goal of this paper is to expound on the concept of celebrity populism, a phenomenon gaining strength across the world but still lacking a credible conceptual underpinning. We rely on two well-established concepts, populism and celebrity politics, to develop a definition of celebrity populism as a powerful formula that combines the attractiveness of populist messages with the awe of celebrity culture. Unlike other conceptualisations of celebrity politics, we differentiate between populist and mainstream (pluralist) politics and suggest that we should evaluate celebrity populism on its own merits, rather than subjugate it to a generic concept of “celebrity politics”. We distinguish three categories of populist celebrity politicians: populist celebrities, celebrity populists, and super celebrity populists. Finally, we test our categorisation on the case of the popular Croatian singer and politician Miroslav Škoro.
Keywords: hrvaški pevci; Miroslav Škora; pevci; Populizem; Slava; Slavni ljudje; zvezdniški populizem; zvezdništvo